PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, GROWTHOPPORTUNITY, LIKUIDITAS, STRUKTUR ASET, RESIKO BISNIS DAN NON DEBT TAX SHIELD TERHADAP STRUKTUR MODAL PADA PERUSAHAAN SUB-SEKTOR BARANG KONSUMSI - TRI PRASETYA, BAGUS (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract:This study was conducted to examine and analyze the effect of profitability, firm size, growth opportunity, liquidity, asset structure, business risk and non-debt tax shield on the capital structure in the consumer goods sub-sector company listed on the Stock Exchange in period 2008-2012. This study used purposive sampling method for sampling, in order to obtain a total of 12 companies by the number N = 60. Analytical method used is multiple regression analysis with the help of analysis tools SPSS version 18.0.Based on the analysis of data it can be concluded that there is influence of variables on capital structure and profitability has a negative direction. While for the variable firm size, growth opportunity, liquidity, asset structure, business risk and non-debt tax shield does not affect the capital structure. Keywords:capital structure, profitability, firm size, growth opportunity, liquidity, asset structure, business risk and non debt tax shield.